The Role of Fintech As East Java’s Economic Growth Drivers: An Empirical Analysis of The Sollow Economic Growth Model - Christien Simorangkir; Maria Agape Widya Prasetya; Yohanes Krisna Purwadi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The COVID-19 pandemic has resulted in a slowdown in national economic growth and Financial Technology (Fintech) has the potential to play a role in economic recovery efforts. East Java is one of the provinces affected by the COVID-19 pandemic but has a very fast development of the financial technology industry prospective. This study aims to analyze how the influence of financial technology on economic growth in East Java within theframework of the Sollow economic growth model. By using the Error Correction Model analysis method for monthly data for the 2019-2020 period, this study provides the results that investment and population have an effect on East Java’s economic growth both in the short term and in the long term. Meanwhile, Fintech lending and commercial bank loans affect economic growth in East Java only in the long term. For this reason, the policyimplication of this research is that there needs to be a program to improve the quality of Human Resources (HR) and a more optimized financial literacy program for the community. Increasing public financial literacy will increase public understanding and use of fintech. Optimizing the use of fintech will become a driving engine for economic growth in East Java.